How performance of the spinning heel kick changes as athletes mature? - Osullivan, D. M.; Prock, M. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: The spinning heel kick is a kick in Taekwondo competition that can be awarded up to 6 points, if it knocks the opponent down. As a result of high potential reward and increase in points allocation, we can observe the spinning heel kick more frequently used in competitions and training. Therefore, the purpose of this study was to investigate how the spinning heel kick`s performance related factors altered as an athlete matures from an elite level junior high-school to university level athlete. METHODS: A total of 48 male taekwondo elite level athletes; 16 middle school, 16 high school, and 16 university, participated. After a taekwondo specific warm up the athletes performed the spinning heel kick a total of 10 times each, under the supervision of their coach and the researchers. While kicking their kinematics was recorded using motion capture system and 2 force plates. The following variables were calculated; total performance time, execution time, preparation time, the width of kicking path mediolaterally, and the maximum kicking foot speed. One way ANOVA was carried out to investigate if there were significant differences between the groups, school level, with Cohen`s d calculated as the effect size. RESULTS: The mean time to perform the spinning hook kick was 0.78 ± 0.06 s for middle school, 0.73 ± 0.06 s for high school and 0.74 ± 0.07s for university athletes. ANOVA revealed no significant differences in performance time among age groups. Likewise, no between group differences were found for preparation time. When comparing the execution time of the spinning hook kick, we found a significant between groups. Post-hoc tests revealed significant differences between middle and high school, and between middle school and university. No differences in execution time were found. The mediolateral width of the kicking path showed no difference. Maximal kicking speed increased with the participants age and was highest for university athletes 10.56 ± 0.95 m/s, followed by high school 9.55 ± 0.80 m/s and middle school athletes 8.30 ± 1.10 m/s. The differences in maximum kicking speed were significant between groups with Post-hoc tests revealing differences between middle vs. high, middle vs. university, and high vs. university. CONCLUSION: This study revealed age related performance differences in the spinning hook kick, with decreasing execution time of the kick and increased maximum kicking speed as the age of participants increased. However, these differences cannot be explained by differences in the preparation of the kick, as the time from the first initiation of the kicking movement until the kicking leg leaves the ground was not affected by age. Also, we found no differences in mediolateral kicking width that might explain differences in execution time and maximum kicking speed due to differences in kicking technique. Future research is therefore needed to identify the reasons leading to the age-related differences found.